Colorectal Cancer - Vannelli, Alberto (IntechOpen, 2021)
Colorectal cancer is the third most common cancer diagnosed in both men and women worldwide. This book examines state-of-the-art research relating to the etiology, diagnosis, prevention and treatment of colorectal cancer. It emphasizes the importance of a multidisciplinary approach involving multiple specialties, including surgery, gastroenterology, radiology, biology, oncology, radiotherapy, nuclear medicine, and physiotherapy.